Concepciones sobre Formación Ciudadana de Líderes Escolares de La Araucanía, Chile - Rebolledo, Patricio Alejandro Lagos; Carrillo Mardones, Olga Aurora; Valdebenito Zambrano, Vanessa Haydee; Villagra Bravo, Carolina; Jurado De Los Santos, Pedro; Donoso Diaz, Sebastian (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
This article studies the explicit conceptions of the school management team about civic education and its relation to the exercise of school leadership at educational facilities in the region of La Araucanía, Chile. The research is highlighted by the enactment of the Law on Civic Education at schools, and follows a qualitative method with an exploratory design, which allows a first approach to the objective of study, providing evidence to the field of civic education. Executives from ten educational institutions were interviewed. Results show diverse concepts and approaches to civic education, which focus on the construct understandings, the human training and their relationship with living in society, values, territory and culture.